2007
DOI: 10.1021/bp060257m
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Increasing the Mass Recovery of Proteins Derived from Inclusion Bodies in Biotechnology

Abstract: A method for increasing the mass recovery of therapeutic proteins produced by E. coli using liquid chromatography was investigated. Recombinant human interferon-gamma (rhIFN-gamma) produced by E. coli was selected as a model therapeutic protein, and hydrophobic interaction chromatography (HIC) was performed as a model for liquid chromatography. Using seven types of stationary phase hydrophobic interaction chromatography (STHIC) with different end groups, the effect of the stationary phase on the mass recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
1
Order By: Relevance
“…In recent years, liquid chromatography (LC) has been used to refold proteins with higher yields (Geng and Wang, 2007; Wang et al, 2004; Jungbauer et al, 2004; Li et al, 2004; Wu et al, 2007). The advantages of the LC method are that it not only prevents the unfolded protein molecules from aggregating with each other, but also purifies or partially purifies the target protein during the chromatographic process, thus it is called protein folding liquid chromatography (PFLC) (Geng and Wang, 2007; Geng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, liquid chromatography (LC) has been used to refold proteins with higher yields (Geng and Wang, 2007; Wang et al, 2004; Jungbauer et al, 2004; Li et al, 2004; Wu et al, 2007). The advantages of the LC method are that it not only prevents the unfolded protein molecules from aggregating with each other, but also purifies or partially purifies the target protein during the chromatographic process, thus it is called protein folding liquid chromatography (PFLC) (Geng and Wang, 2007; Geng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A monograph and review paper of PFLC was recently published to introduce this new kind of LC as a tool for protein folding in molecular biology [29][30][31]. It was reported that ion exchange chromatography (IEC), size exclusion chromatography (SEC), hydrophobic interaction chromatography (HIC), and affinity chromatography can be employed to have either all, or some of these four functions simultaneously [32][33][34][35][36]. Also many types of chromatography, such as expanded bed chromatography (EBC) [37,38], continuous annular chromatography (CAC) [39][40][41], simulated moving bed chromatography (SMBC) [42,43], and chromatographic cake [44][45][46][47][48][49] have been successfully used in PFLC at both the small and large scales, this will be discussed further in Section 4.2.2.…”
Section: Protein Folding Liquid Chromatography (Pflc)mentioning
confidence: 99%
“…If little precipitates form on the surface of the filter above the top of the cake, it only blocks a very small fraction of the total filter surface, not affecting the chromatographic run. Wu et al [32] reported that periodically washing the cake with a strong solvent, acted not only in re-dissolving the precipitates, which formed, but also increased both the mass and bioactive recovery of the target protein. Geng et al [46] reported on a new technology for the purification with simultaneous renaturation of rhIFN-␥ from E. coli using a large size (1 cm in length and 30 cm in diameter packed with HIC packing material) chromatographic cake, in this instance, this cake was referred to as "the unit of simultaneous renaturation and purification of protein (USRPP)" An extract containing 2 g of rhIFN-␥ in a 7.0 M GuHCl solution of 700 mL was directly pumped into the large cake for renaturation with simultaneous purification.…”
Section: Column For Protein Foldingmentioning
confidence: 99%
“…These materials are commercially available over a wide range of molecular weights ranging from 300 g mol À1 to tens of thousands [1] and soluble in water and most of organic solvents such as methylene chloride, ethanol, toluene, acetone, and chloroform [2,3]. Especially, the PEGs are non-toxic, low volatile, and biodegradable and thus they are considered as "green" solvents [4][5][6][7][8][9][10][11]. When PEGs are used in industry, they generally mixed with alcohols to form microemulsions or various solubilized systems.…”
Section: Introductionmentioning
confidence: 99%